2020
DOI: 10.1108/prt-08-2019-0070
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidative degradation of indigo wastewater based on chlorine-containing system

Abstract: Purpose In this study, the oxidative degradation performance of indigo wastewater based on electrochemical systems was explored. The decolourization degrees, removal rate of chemical oxygen demand and biochemical oxygen demand of the indigo wastewater after degradation were evaluated and optimized treatment conditions being obtained. Design/methodology/approach The single factor method was first used to select the electrolyte system and electrode materials. Then the response surface analysis based on Box–Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Also the deeper the color, the more signicant the factor. [28][29][30] In Fig. 4(1), the three-dimensional response surface plots showed that with the increase of initiator concentration and the mass ratio of total monomer to chitosan, the graing rate increased rst and then decreased.…”
Section: Response Surface Analysismentioning
confidence: 99%
“…Also the deeper the color, the more signicant the factor. [28][29][30] In Fig. 4(1), the three-dimensional response surface plots showed that with the increase of initiator concentration and the mass ratio of total monomer to chitosan, the graing rate increased rst and then decreased.…”
Section: Response Surface Analysismentioning
confidence: 99%